Precipitation of Hydroxyapatite at 37 degrees C in a Meso Oscillatory Flow Reactor Operated in Batch at Constant Power Density - Filipa Castro (2013)
A meso oscillatory flow reactor (meso-OFR) was successfully applied for the precipitation of hydroxyapatite (HAp) nanoparticles. Mixing efficiency of the mesoreactor operated batchwise in a vertical tube was evaluated at constant power density, by monitoring variation of hue values upon mixing both spatially and temporally. The best operating conditions for fast mixing and a more homogeneous reaction medium were verified for f=0.83 Hz and x(0)=4.5 mm. HAp precipitation was then carried out under these conditions at 37 degrees C for different mixing Ca/P molar ratios. HAp nanoparticles with a mean size (d(50)) of about 67 nm and a narrow size distribution were obtained. Furthermore, the obtained results show the advantages of the meso-OFR over a stirred tank batch reactor due to the production, about four times faster, of smaller and more uniform HAp nanoparticles. (c) 2013 American Institute of Chemical Engineers AIChE J, 59: 4483-4493, 2013